1988
DOI: 10.1007/bf00193743
|View full text |Cite
|
Sign up to set email alerts
|

Studies on sporopollenin biosynthesis in Tulipa anthers

Abstract: Extensive tracer experiments were carried out on Tulipa with the aim of determining the structure and biosynthesis of sporopollenin. The radiolabeled precursors were applied using an improved technique previously selected. The sporopollenin fraction was purified using either a gentle method -hydrolyzing enzymes (pronase, amylase, amyloglucosidase, cellulase, pectinase and lipase) and alkaline hydrolysis (method A) -or by a conventional aggressive procedure, where the material was enriched by alkaline hydrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…FTIR (Fourier transform infrared) studies by Kawase et al agreed with a high proportion of aliphatic units and suggested that possibly the aliphatic core of sporopollenin shares a common biosynthesis among all different taxa and vascular plants in particular [ 52 , 53 ]. This means that each type of plant produces different aromatic side chains, which could differentiate pollen grain and spores at a microscopic level by both morphology and chemical structure [ 43 , 54 , 55 , 56 , 57 , 58 ]. Further solid-state NMR studies provided more data with more detail on the structure showing that the core comprises of tetra-, hexa-, and octa-cosanes.…”
Section: Chemical Structure Of Pollen Shells (Sporopollenin)mentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR (Fourier transform infrared) studies by Kawase et al agreed with a high proportion of aliphatic units and suggested that possibly the aliphatic core of sporopollenin shares a common biosynthesis among all different taxa and vascular plants in particular [ 52 , 53 ]. This means that each type of plant produces different aromatic side chains, which could differentiate pollen grain and spores at a microscopic level by both morphology and chemical structure [ 43 , 54 , 55 , 56 , 57 , 58 ]. Further solid-state NMR studies provided more data with more detail on the structure showing that the core comprises of tetra-, hexa-, and octa-cosanes.…”
Section: Chemical Structure Of Pollen Shells (Sporopollenin)mentioning
confidence: 99%
“…The presence of phenolic groups in sporopollenin was showed using FTIR spectroscopy [ 69 ]. There are indications that phenols (particularly p -coumaric and ferulic acids) are not just involved as side chains within the core [ 52 , 70 ] but also in the cross-linking of the polymer [ 43 , 46 , 47 , 57 , 58 , 66 , 67 ].…”
Section: Chemical Structure Of Pollen Shells (Sporopollenin)mentioning
confidence: 99%
“…It is not soluble in any known solvent. Elemental analysis [3], ozonolytic oxidation [4], solid state NMR [5], IR [6] and fluorescence spectroscopy [7], as well as isotope labelling [8,9] hint to a crosslinked aromatic-aliphatic polyether-ester compound, * This paper was presented at the 15th Chitose International Forum "Nanotechnology -From Synthesis to Devices," Chitose Institute of Science and Technology, Chitose, Japan, October 2-3, 2014. † Corresponding author: kart@photon.chitose.ac.jp which is formed during pollen morphogenesis while the tapetum wall around the pollen tetrad dissolves [10,11].…”
Section: Introductionmentioning
confidence: 99%